The Effectiveness of Flipbook Learning in Sports Physiology Courses Improves Student Achievement In the course of the Pandemic - Ratno Susanto; Achmad Afandi; Farizha Irmawati (JUMORA: Jurnal Moderasi Olahraga, 2022)
This study aims to provide an overview of the persuasiveness of flipbooks and education in the COVID 19 pandemic, an Omicron variant of the sports physiology course. The study is a descriptive quantitative study that evaluates educational flipbooks in a course of exercise physiology. The subjects of the study are the second semester of the 2020 class students who are taught in the exercise physiology course using virtual flipbooks. The study sample is the second semester of 2020 undergraduates whose location was selected using a simple random sampling technique, taking into account population uniformity. I will go to collect musical instruments in the flip book learning questionnaire. Engagement analysis used descriptive statistics. Consequence showed so students assessed that learning sports physiology apply flipbooks was effective (23.3%), rated it as productive (46.7%), along time placed average (20%). Handful students think about online education flipbooks failed (10%) and totally none (0%) who rate it very inefficient. Finally, to better the quality of flipbook learning in sports physiology in the course of the omicron variant of covid19 pandemic, schoolteacher must realize suggestions from respondents, namely: (1) studying is execute through video calls; (2) equipping of concise study materials; (3) minimizing dispatch material in the form of heavy videos to save quota with flipbook application; (4) the selection material flipbook on the criteria of language easy to understand; (5) continue lay out material before assignment; (6) display varied and contrasting questions for each student; (7) occupation include how it works; (8) assign occupation according course schedule; (9) prompt students an occupation given, with (10) reduce the task. Keywords: Abstract in English about 3-6 words, sorted alphabetically